2009
DOI: 10.1021/nl903366z
|View full text |Cite
|
Sign up to set email alerts
|

Black Ge Based on Crystalline/Amorphous Core/Shell Nanoneedle Arrays

Abstract: Direct growth of black Ge on low-temperature substrates, including plastics and rubber is reported. The material is based on highly dense, crystalline/amorphous core/shell Ge nanoneedle arrays with ultrasharp tips ( approximately 4 nm) enabled by the Ni catalyzed vapor-solid-solid growth process. Ge nanoneedle arrays exhibit remarkable optical properties. Specifically, minimal optical reflectance (<1%) is observed, even for high angles of incidence ( approximately 75 degrees ) and for relatively short nanoneed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 28 publications
(21 reference statements)
4
77
0
1
Order By: Relevance
“…Some pioneering methods have been demonstrated that can be used to construct arrays based on amorphous nanomaterials, such as pulsed laser deposition (PLD) [70], electrochemical oxidation [71,72], reactive ion etching (RIE) [73], solution-based self-assembly [74] and CVD [75].…”
Section: Nanosheetsmentioning
confidence: 99%
“…Some pioneering methods have been demonstrated that can be used to construct arrays based on amorphous nanomaterials, such as pulsed laser deposition (PLD) [70], electrochemical oxidation [71,72], reactive ion etching (RIE) [73], solution-based self-assembly [74] and CVD [75].…”
Section: Nanosheetsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, the optical properties of arrays of nano-and microscale wires have been exploited for enhanced light absorption in photovoltaic devices, [16][17][18][19] however, the ability to substantially manipulate absorption in individual nanoscale structures has not been well established. In order to quantify optical resonances supported in individual NWs, scattering [20][21][22] and absorption cross-sections 5,6,11,[23][24][25][26] have been measured or calculated.…”
mentioning
confidence: 99%
“…For example, these NNs can be utilized as sensitive typical probe-tips in atomic force microscopy (AFM) due to their very small apex angle (h $ 5°), allowing a superior scanning of the sample surface profile with high spatial resolution [55]. Furthermore, these ultra-sharp SiNNs possessing high absorption coefficient are prospective for efficient solar cell applications [56][57][58]. In short, present findings attest to the validity of size-controlled growth process, where SiNNs dimension can precisely be improved by optimizing the catalyst morphology and other processing parameters.…”
Section: Resultsmentioning
confidence: 99%